Analysis of Factors Affecting Indonesian Coffee Exports in 2001-2018 Using The Vector Autoregression (VAR) Approach - Diandra Locita Sari; Sugeng Hadi Utomo (Journal Research of Social Science, Economics, and Management, 2021)
Coffee exports are influenced by the exchange rate, the price of coffee and the amount of production. The purpose of the study was to determine the short-term and long-term relationship between coffee exports in 2001-2018. The research method is quantitative descriptive using classical assumption test and Error Correlation Model (ECM). The results of the VAR study are that coffee exports are not affected by coffee prices, coffee production and the rupiah exchange rate. Coffee exports were not significantly affected by coffee production, coffee prices and the exchange rate (exchange rate) using VAR. result Grangger's is that coffee production affects coffee exports and the exchange rate affects coffee exports. Test IRF and VD is the coffee production is influenced by coffee prices and the exchange rate, the price of coffee affects the production of coffee, coffee exports and the exchange rate and the exchange rate is influenced by the price of coffee and coffee exports. As for advice because coffee production affects coffee exports from Indonesia then, the government should do a vertical integration from upstream (people's plantations) to downstream (industries) to increase export expansion.